2000
DOI: 10.1177/104063870001200204
|View full text |Cite
|
Sign up to set email alerts
|

Canines as Sentinels for Lyme Disease in San Diego County, California

Abstract: Abstract. Prevalence of Lyme borreliosis in canine sentinels has been shown to correlate with infection in humans. One thousand canine sera (917 dogs, 83 coyotes) obtained from animal control authorities and area veterinarians were screened by ELISA for antibodies to Borrelia burgdorferi. Results were validated by Western blot and indirect fluorescent antibody (IFA) tests at referee laboratories. Criterion for a positive Western blot was presence of 5 of 10 of the most common antigen IgG bands; for IFA, Ͼ1:128… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Any negative interactions from this A. sagrei invasion may have the potential to change mechanisms of the tick-Lyme disease interaction in southern California (Swei et al, 2011). There is some evidence to suggest mechanisms could be changing with Lyme disease detected in dog sera of urban San Diego dogs in the highest prevalence, compared to natural habitats, suggesting that changes in S. occidentalis populations could be relevant to disease prevalence change over time, even in the urban landscape (Olson et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Any negative interactions from this A. sagrei invasion may have the potential to change mechanisms of the tick-Lyme disease interaction in southern California (Swei et al, 2011). There is some evidence to suggest mechanisms could be changing with Lyme disease detected in dog sera of urban San Diego dogs in the highest prevalence, compared to natural habitats, suggesting that changes in S. occidentalis populations could be relevant to disease prevalence change over time, even in the urban landscape (Olson et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, no study has reported on the association between Bb detected in I. scapularis collected from deer and human LD. Furthermore, dogs have been extensively studied as suitable sentinels for human LD (Lindenmayer et al., 1991; Daniels et al., 1993; Olson et al., 2000; Duncan et al., 2005; Hamer et al., 2009). A few of these studies, however, assessed the association between human and dog LD (Lindenmayer et al., 1991; Daniels et al., 1993; Guerra et al., 2001) using serum samples.…”
Section: Introductionmentioning
confidence: 99%
“…Because of this, mammalian predators have been the focus of numerous disease investigations and have been recommended as sentinels for wildlife and zoonotic diseases (Thomas and Hughes, 1992;Mitchell et al, 1999;Olson et al, 2000). Coyotes (Canis latrans) and raccoons (Procyon lotor) are ideal candidates for surveillance studies because both species are common and widespread in North America (Bekoff, 1982;Kaufmann, 1982).…”
mentioning
confidence: 99%